charlie and the great glass elevator - Dahl, Roald; Roald Dahl (New York Penguin Group Inc., 1972)
Now that he's won the chocolate factory, what's next for charlie? Last seen flying through the sky in a giant elevator in charlie and the chocolate factory, charlie bucket's back for another adventure. When giant elevator picks up speed, charlie, willy wonka, and the gang are sent hurting through space and time. Visiting the world's first space hotel, battling the dreaded vermicious knids, and saving the world are only a few stops along this remarkable , intergalactic joyride.
English